On general solution of ode system for modeling stationary compressible flow of perfect gas with constant heat flux and friction in the constant-area channel - Fedorov, M. (Proceedings of National Aviation University (archive), 2002)
The possibility is demonstrated of taking a general solution of the differential equation systemdescribing one-dimensional stationary flow of compressible gas with the given constant heatflux, friction and mass forces that can perform work in the constant-area channel.